Kindergarten teachers’ perspectives on English vocabulary stimulation for young children through digital games - Elise muryanti; Yuli Herman (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study examines kindergarten teachers’ perceptions of using digital games to improve young children’s English vocabulary and investigates the mediating role of cognitive development in learning effectiveness. A mixed-method sequential explanatory design was employed. Quantitative data were collected from 87 kindergarten teachers in Padang using a Likert-scale questionnaire and analyzed with PLS-SEM, followed by semi-structured interviews with six teachers and thematic analysis. Digital games had no significant direct effect on vocabulary learning effectiveness (p = 0.082), but significantly enhanced children’s cognitive development, which mediated learning effectiveness. Cognitive development is a key mechanism through which digital games support vocabulary learning. Strengthening teachers’ digital pedagogical competence and selecting age-appropriate digital content are essential to maximize vocabulary acquisition in early childhood education.